Westonci.ca is the best place to get answers to your questions, provided by a community of experienced and knowledgeable experts. Discover solutions to your questions from experienced professionals across multiple fields on our comprehensive Q&A platform. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
To solve the given problem, we need to find the value of [tex]\( x \)[/tex] that satisfies the equation
[tex]$(3 \vec{i} - 2 \vec{j} + 2 \vec{k}) \cdot (2 \vec{i} - x \vec{j} + 3 \vec{k}) = -12.$[/tex]
This equation involves the dot product of two vectors. The dot product of two vectors [tex]\( \vec{a} = a_1 \vec{i} + a_2 \vec{j} + a_3 \vec{k} \)[/tex] and [tex]\( \vec{b} = b_1 \vec{i} + b_2 \vec{j} + b_3 \vec{k} \)[/tex] is given by
[tex]\[ \vec{a} \cdot \vec{b} = a_1 b_1 + a_2 b_2 + a_3 b_3. \][/tex]
Now, let's identify the components of our vectors:
- For the vector [tex]\( 3 \vec{i} - 2 \vec{j} + 2 \vec{k} \)[/tex]:
- [tex]\( a_1 = 3 \)[/tex]
- [tex]\( a_2 = -2 \)[/tex]
- [tex]\( a_3 = 2 \)[/tex]
- For the vector [tex]\( 2 \vec{i} - x \vec{j} + 3 \vec{k} \)[/tex]:
- [tex]\( b_1 = 2 \)[/tex]
- [tex]\( b_2 = -x \)[/tex]
- [tex]\( b_3 = 3 \)[/tex]
Substitute these components into the dot product formula:
[tex]\[ (3 \vec{i} - 2 \vec{j} + 2 \vec{k}) \cdot (2 \vec{i} - x \vec{j} + 3 \vec{k}) = 3 \cdot 2 + (-2) \cdot (-x) + 2 \cdot 3. \][/tex]
We can now simplify and solve for [tex]\( x \)[/tex]:
[tex]\[ 3 \cdot 2 + (-2) \cdot (-x) + 2 \cdot 3 = 6 + 2x + 6. \][/tex]
Combine like terms:
[tex]\[ 6 + 2x + 6 = 12 + 2x. \][/tex]
We set the dot product equal to [tex]\(-12\)[/tex] as given in the problem:
[tex]\[ 12 + 2x = -12. \][/tex]
To isolate [tex]\( x \)[/tex], we first subtract 12 from both sides:
[tex]\[ 2x = -12 - 12, \][/tex]
which simplifies to:
[tex]\[ 2x = -24. \][/tex]
Next, we divide both sides by 2 to solve for [tex]\( x \)[/tex]:
[tex]\[ x = \frac{-24}{2} = -12. \][/tex]
This tells us that the value of [tex]\( x \)[/tex] is [tex]\(-12\)[/tex].
Thus, the correct answer is:
[tex]\[ \boxed{-12} \][/tex]
[tex]$(3 \vec{i} - 2 \vec{j} + 2 \vec{k}) \cdot (2 \vec{i} - x \vec{j} + 3 \vec{k}) = -12.$[/tex]
This equation involves the dot product of two vectors. The dot product of two vectors [tex]\( \vec{a} = a_1 \vec{i} + a_2 \vec{j} + a_3 \vec{k} \)[/tex] and [tex]\( \vec{b} = b_1 \vec{i} + b_2 \vec{j} + b_3 \vec{k} \)[/tex] is given by
[tex]\[ \vec{a} \cdot \vec{b} = a_1 b_1 + a_2 b_2 + a_3 b_3. \][/tex]
Now, let's identify the components of our vectors:
- For the vector [tex]\( 3 \vec{i} - 2 \vec{j} + 2 \vec{k} \)[/tex]:
- [tex]\( a_1 = 3 \)[/tex]
- [tex]\( a_2 = -2 \)[/tex]
- [tex]\( a_3 = 2 \)[/tex]
- For the vector [tex]\( 2 \vec{i} - x \vec{j} + 3 \vec{k} \)[/tex]:
- [tex]\( b_1 = 2 \)[/tex]
- [tex]\( b_2 = -x \)[/tex]
- [tex]\( b_3 = 3 \)[/tex]
Substitute these components into the dot product formula:
[tex]\[ (3 \vec{i} - 2 \vec{j} + 2 \vec{k}) \cdot (2 \vec{i} - x \vec{j} + 3 \vec{k}) = 3 \cdot 2 + (-2) \cdot (-x) + 2 \cdot 3. \][/tex]
We can now simplify and solve for [tex]\( x \)[/tex]:
[tex]\[ 3 \cdot 2 + (-2) \cdot (-x) + 2 \cdot 3 = 6 + 2x + 6. \][/tex]
Combine like terms:
[tex]\[ 6 + 2x + 6 = 12 + 2x. \][/tex]
We set the dot product equal to [tex]\(-12\)[/tex] as given in the problem:
[tex]\[ 12 + 2x = -12. \][/tex]
To isolate [tex]\( x \)[/tex], we first subtract 12 from both sides:
[tex]\[ 2x = -12 - 12, \][/tex]
which simplifies to:
[tex]\[ 2x = -24. \][/tex]
Next, we divide both sides by 2 to solve for [tex]\( x \)[/tex]:
[tex]\[ x = \frac{-24}{2} = -12. \][/tex]
This tells us that the value of [tex]\( x \)[/tex] is [tex]\(-12\)[/tex].
Thus, the correct answer is:
[tex]\[ \boxed{-12} \][/tex]
We appreciate your time on our site. Don't hesitate to return whenever you have more questions or need further clarification. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. We're glad you visited Westonci.ca. Return anytime for updated answers from our knowledgeable team.